تفسیر المنار میں قصص قرآنی کی تعبیرات: ایک مطالعہ: A Study of Interpretations of Quranic Stories in Tafsīr al-Manār (Al-Qamar, 2025)
This article explores the interpretative approach of Allama Rashid Radha towards the Qur’anic narratives (Qasas al-Qur’an) in his renowned exegesis, Tafsir al-Manar. Diverging from traditional exegetical methods, Radha employs a rational and analytical framework to present these narratives in a manner that resonates with the modern intellect. While classical interpretations often emphasize historical details and rely heavily on transmitted reports, including Isra'iliyyat, Rida seeks to uncover the underlying wisdom, moral lessons, and universal messages within the stories. He interprets miracles and events not merely as supernatural occurrences but within the bounds of reason and scientific plausibility. This rationalist methodology not only avoids mythological tendencies but also enhances the ethical and practical relevance of the narratives for contemporary readers. The article highlights how Rashid Rida's approach redefines the purpose of Qur’anic stories—not as tales of the past, but as enduring sources of guidance and reflection.
Keywords: Qur’anic Narratives, Tafsir al-Manar, Rashid Rida, Rational Interpretation, Islamic Exegesis, Isra'iliyyat, Qur’an and Modernity, Qur’anic Stories, Miracles in the Qur’an, Moral Lessons in the Qur’an